2018
DOI: 10.3390/met8060407
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior Difference in Initial Period for Hot-Rolled and Cold-Rolled 2205 Duplex Stainless Steels

Abstract: Precipitate phases often play an important role on the corrosion resistance of 2205 Duplex stainless steels (DSS). In the present paper, the microstructure and the corrosion resistance of the hot-rolled and cold-rolled 2205 steels aged for different times at 850 • C was investigated through XRD, SEM, and potentiodynamic polarization. It was discovered that the Chi(χ) phase and Sigm(σ) phase were precipitated in turn following the aging treatment of the hot-rolled and cold-rolled steels, but the precipitate amo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…Además de las fases mayoritarias α y γ, se puede presentar una variedad de fases secundarias indeseables que se forman por efecto de los elementos aleantes y de los tratamientos térmicos, entre ellas destacan los nitruros hexagonales (Cr 2 N), fase sigma (σ), fase chi (χ), austenita secundaria (γ 2 ), fase R, fase π, fase G, M 7 C 3 , M 23 C 6 y fase τ (Gunn, 1997;Mateo y Llanes, 1997;Karlsson, 1999). La precipitación de pequeñas cantidades de las fases χ y σ afecta drásticamente a las propiedades mecánicas y de resistencia a la corrosión características de estos aceros (Gironès et al, 2007;Fargas et al, 2009;Gao et al, 2018). La fase σ es una fase intermetálica no magnética, de estructura tetragonal, cuya precipitación es observada en un rango de temperaturas entre los 600 y 1000 ºC y ocurre principalmente a través de la descomposición eutectoide de α en σ y γ 2 .…”
Section: Introductionunclassified
“…Además de las fases mayoritarias α y γ, se puede presentar una variedad de fases secundarias indeseables que se forman por efecto de los elementos aleantes y de los tratamientos térmicos, entre ellas destacan los nitruros hexagonales (Cr 2 N), fase sigma (σ), fase chi (χ), austenita secundaria (γ 2 ), fase R, fase π, fase G, M 7 C 3 , M 23 C 6 y fase τ (Gunn, 1997;Mateo y Llanes, 1997;Karlsson, 1999). La precipitación de pequeñas cantidades de las fases χ y σ afecta drásticamente a las propiedades mecánicas y de resistencia a la corrosión características de estos aceros (Gironès et al, 2007;Fargas et al, 2009;Gao et al, 2018). La fase σ es una fase intermetálica no magnética, de estructura tetragonal, cuya precipitación es observada en un rango de temperaturas entre los 600 y 1000 ºC y ocurre principalmente a través de la descomposición eutectoide de α en σ y γ 2 .…”
Section: Introductionunclassified
“…It can be mentioned that the strain-induced martensite (SIM) could be formed, and it has the same crystallographic parameters as the ferrite, so ferrite and α'-martensite peaks are coincident. Recent studies have shown a consistent decrease in austenite with increased deformation as indicative of SIM 18,[33][34][35][36][37][38] . Furthermore, studies indicate that the peak (200)γ disappearance after cold rolling is due to the SIM formation 20,35,39,40 .…”
Section: Microstructure Evolutionmentioning
confidence: 90%
“…Furthermore, it modifies the composition of the passive film at room temperature and the results show a less protective ability of the passive film with an increase in deformation level of 2205 DSS duplex stainless steel in simulated concrete pore solution. Gao et al 37 studied 2205 DSS in a 3.5% NaCl solution and the results indicate that σ phase, strain-induced martensite, as well as the defects, induced by cold deformation, lower the corrosion resistance.…”
Section: Passive Propertiesmentioning
confidence: 99%
“…[14] While an initial low crystallographically coherent interface between α and γ phases enhances σ phase precipitation. [15] In addition, it is because of the presence of σ-phase in the austenite/ferrite microstructure of DSSs reduces their lifetime and promotes a brittle fracture in service, [16][17][18][19][20] more research is devoted to reducing the precipitation of this phase by proper heat treatment. Elmer et al [21] studied the precipitation of the σ phase in 2205 DSSs using in situ observation method and found that the σ phase was detected only after aging at 850 °C for 81 s; the precipitation amount reached 13.4% after 30 min, while it will completely dissolve after raising the temperature to 985 °C.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,12 ] At high temperatures, the σ phase is mainly at the ferrite ( α )/austenite ( γ ) phase boundary and the α grain boundary, and the growth mechanism is the transformation of the α phase to the σ and the γ 2 phases. [ 14–20 ] Furthermore, thermokinetic predictions confirm that the segregation of Cr and especially Mo at grain boundaries of α plays an important role in the nucleation of σ phase. [ 14 ] While an initial low crystallographically coherent interface between α and γ phases enhances σ phase precipitation.…”
Section: Introductionmentioning
confidence: 99%